Figurative Language In Secondhand Serenade A Naked Twist In My Story Album - Andy Amirudin; Dice Anggraini Malta (Fakultas Sastra Universitas Ekasakti, 2022)
This research analysis of figurative language and meaning contained in the lyrics of the song Secondhand Serenade a naked Twist in My Story Album. This research applies semantic theory, especially to figurative language and meaning. The theory used in analyzing figurative language by Kennedy (1995) and the use of meaning in the lyrics used Leech's (1981) theory. The purposes of this research are: (1) To analyze figurative language contained in each lyrics in the album A Naked Twist in My Story. (2) To analyze meaning countained in each lyrics in album A Naked Twist In My Story. This research used this research is the qualitative method. The technique of analyze the data in this research used to substitutional technique. The data collection technique used in the research is observation technique and noted taking technique. The data source is taken from Secondhand Serenade a Naked Twist in My Story Album. The data analysis of this research is to follow the following steps: selecting songs that contain figurative language and meanig, identifying types of figurative language by reading carefully, classifying type offigurative language from the data, and making conclusions. The results of this research show that the total number of figurative languages used in the lyrics in secondhand serenade are 36 figurative language data and 15 meanings. The data of figurative language includes 3 data of metaphor, 2 data of simile, 11 data of personification, 17 data of hyperbole, 2 data of metonymy, 2 data of synecdoche and 4 data of paradox. While the meaning of the data contained in the research there are 15 data, namely 4 data of conceptual meaning and 11 data of connotative meaning.